Hydrothermal synthesis of Carbon Quantum Dots: an updated review - Nazibudin, Nazatul Akmal; Zainuddin, Mohammad Faiz; Che Abdullah, Che Azurahanim (Akademia Baru Publishing, 2023)
Carbon Quantum Dots (CQDs) have exceptionally solid and tuneable fluorescence properties which empower their application in vast fields. The hydrothermal approach is regarded as direct and efficient, through polymerization and carbonization reactions, and has been widely applied to prepare various materials due to the high reactivity of the reactants, easy control of the solution, little harm to the environment and low energy consumption under hydrothermal condition. The attracting feature of this route is that neither any strong acid nor post-synthetic surface passivation is necessary. As of now, a lot of important progress in the hydrothermal synthesis of carbon quantum dots such as materials use as precursors and influence of hydrothermal synthesis parameters. Hydrothermal synthesis is one of the most commonly used methods for preparation of nanomaterials. It is basically a solution reaction-based approach. In this review, the main focus is to review the hydrothermal route for carbon quantum dots using different source of materials and their fundamental characterizations, followed by the influence of hydrothermal synthesis conditions to carbon quantum dots.